2015
DOI: 10.4103/1119-3077.151737
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported sleep parameters among secondary school teenagers in middle-belt Nigeria

Abstract: A substantial number of students had borderline nighttime sleep duration and so had potentials to transit into the problematic insufficient range. To prevent this, there is a need to educate schooling teenagers on the dangers associated with prolonged sleep insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
2
13
1
Order By: Relevance
“…In the United Kingdom, children start school at around 8.45 a.m., unlike 8 a.m. in Nigeria, which means that children in Nigeria have to get‐up earlier. Another striking finding in this study was the shorter night sleep duration in our participants when compared with secondary school teenagers from Benue in northwest Nigeria , which supports the possible influence of environmental factors, modern civilisation and changes in lifestyle. Because Lagos is a major economic centre in Nigeria, it is densely populated with heavy traffic and getting to any destination on time can be challenging.…”
Section: Discussionsupporting
confidence: 74%
“…In the United Kingdom, children start school at around 8.45 a.m., unlike 8 a.m. in Nigeria, which means that children in Nigeria have to get‐up earlier. Another striking finding in this study was the shorter night sleep duration in our participants when compared with secondary school teenagers from Benue in northwest Nigeria , which supports the possible influence of environmental factors, modern civilisation and changes in lifestyle. Because Lagos is a major economic centre in Nigeria, it is densely populated with heavy traffic and getting to any destination on time can be challenging.…”
Section: Discussionsupporting
confidence: 74%
“…The use of electronic communication gadgets is one extrinsic factor that has been reported to influence sleep among adolescents. [ 16 17 18 19 20 21 ] We also found that up to 42.8% of the adolescents are frequently involved with the social media till <1 h before sleep time. This practice was most prevalent among those in the late adolescent age group though the difference across the age groups was not statistically significant.…”
Section: Discussionmentioning
confidence: 64%
“…However, Sanya et al . [ 16 ] in Ilorin, Nigeria reported mean sleep duration of 9.33 ± 2.29 h during school days which is optimal in adolescence. Although our finding agrees with most others, the difference with Sanya et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A research to male students in Nigeria shows that their daily sleeping duration is 7.42 hours/day, standing time of 1.92 hours/day, and private activity of 1.57 hours/day 15 . In Nigerian teenagers Students' mean sleep duration during school days was 9.33 ± 2.29 h compared to 10.09 ± 1.32 h at weekend (P < 0.05) 16 .The research to sleeping in EC group (Eating competent) in United States of America shows that they have higher proportion of sleeping quality (67% vs 57% in non-EC, p = 0,001), sleeping duration of ≥ 7 hours (58% vs 50% in non-EC, p = 0,007), and time disfunction (72% vs 65% in non-EC, p = 0,02) 17 .…”
Section: Discussionmentioning
confidence: 99%